EXPLORATION OF THE PHYTOCHEMICAL CONTENT OF Murraya paniculata L. AS TRADITIONAL MEDICINE : A REVIEW - Aini, Qurratu; Fajriana, Nurul (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2024)
Murraya paniculata L., Jack (Kemuning) is a traditional medicinal plant that has great potential in treating various diseases but is still not scientifically researched. The urgency of this research lies in the need to develop safe and effective kemuning-based traditional medicine through a deeper understanding of its phytochemical content and pharmacological activity. This study aims to explore and identify active compounds in Murraya paniculata L., as well as evaluate their pharmacological potential. This plant is widely used as an anti-inflammatory, antimicrobial, antidiabetic, antihyperlipidemic, antinociceptive, anticarcinogenic, antiaging, antitumor, analgesic activity, treating asthma, melanogenesis and tyrosinase activity. It is hoped that this research can make a significant contribution to the development of traditional medicine based on Indonesian natural resources and increase the use of kemuning in modern medicine.